2002
DOI: 10.1021/ja026879v
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of a Genomically Encoded Fosfomycin Resistance Protein (FosA) at 1.19 Å Resolution by MAD Phasing Off the L-III Edge of Tl+

Abstract: The fosfomycin resistance protein (FosA) catalyzes the Mn(II)- and K+-dependent addition of glutathione to the oxirane of the antibiotic fosfomycin. The crystal structure of FosA from Pseudomonas aeruginosa was solved at a resolution of 1.19 A by multiwavelength anomalous diffraction at the L-III edge of a Tl+ derivative. The structure solution took advantage of the ability of Tl+ to substitute for K+. The existence of multiple Tl sites in the asymmetric unit suggests that this may be a generally useful techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
118
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(123 citation statements)
references
References 24 publications
5
118
0
Order By: Relevance
“…The initial geometry was built from the X-ray structure of FosA from P. aeruginosa complexed with fosfomycin (PDB code: 1LQP, resolution 1.19 Å). 13 The dimeric form was used, and an active region for the setup was selected containing residues within 30 Å of the Mn atom of chain A. The protonation states of the titratable residues (His, Asp, and Glu) were determined on the basis of their pK a values obtained via the PROPKA 51 program (see Supporting Information for details) and verified by visual inspection of the hydrogen-bonding environment of the residues assuming pH = 8 (the working pH of FosA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The initial geometry was built from the X-ray structure of FosA from P. aeruginosa complexed with fosfomycin (PDB code: 1LQP, resolution 1.19 Å). 13 The dimeric form was used, and an active region for the setup was selected containing residues within 30 Å of the Mn atom of chain A. The protonation states of the titratable residues (His, Asp, and Glu) were determined on the basis of their pK a values obtained via the PROPKA 51 program (see Supporting Information for details) and verified by visual inspection of the hydrogen-bonding environment of the residues assuming pH = 8 (the working pH of FosA).…”
Section: Methodsmentioning
confidence: 99%
“…As mentioned in the Introduction, the crystal structure of FosA in complex with fosfomycin has a water-accessible open pocket. 13 However, water addition is not catalyzed by FosA, but by another enzyme (FosX). 15−17 Theoretical calculations gave very similar barriers for alcohol and thiol attack on amide, 74 and for thiolysis and alcoholysis of phosphate monoester, 75 so that one might expect similar reactivity for GSH and water attack on fosfomycin.…”
Section: Qm Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there is no significant sequence similarity between FosA and the cytosolic (members of the alpha, pi, mu, sigma, theta, zeta, or kappa classes) GSTs. However, the three-dimensional structure of FosA from Pseudomonas aeruginosa exhibits similarity to members of the vicinal oxygen chelate family such as glyoxalase I and the extradiol dioxygenases (19), which are characterized by the ability to bind a metal cofactor with available sites for substrate coordination (20 -22).…”
mentioning
confidence: 99%
“…The crystal structure of substrate-bound FosA showed that, like other members of the vicinal oxygen chelate family, fosfomycin binds at the active site Mn 2ϩ with distances of 2.0 Å between Mn 2ϩ and one of the phosphonate oxygens and 2.4 Å between Mn 2ϩ and the oxirane oxygen of fosfomycin (Scheme 1) (19). The crystal structure also revealed a number of amino acids (Thr ) that interact with the bound fosfomycin at the active site (Fig.…”
mentioning
confidence: 99%